2012
DOI: 10.1093/mnras/sts307
|View full text |Cite
|
Sign up to set email alerts
|

A Gemini ground-based transmission spectrum of WASP-29b: a featureless spectrum from 515 to 720 nm

Abstract: We report Gemini-South GMOS observations of the exoplanet system WASP-29 during primary transit as a test case for differential spectrophotometry. We use the multi-object spectrograph to observe the target star and a comparison star simultaneously to produce multiple light curves at varying wavelengths. The 'white' light curve and fifteen 'spectral' light curves are analysed to refine the system parameters and produce a transmission spectrum from ∼515 to 720 nm. All light curves exhibit time-correlated noise, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(84 citation statements)
references
References 31 publications
6
78
0
Order By: Relevance
“…Also, day-side spectral features may be absent due to an isothermal pressuretemperature profile (Fortney et al 2006). These planets are consistent with other transiting exoplanet observations with flat spectra in optical wavelengths on TrES-3b , GJ 3470b (a hot Uranus; Biddle et al 2014), GJ 1214b (Bean et al 2011;Kreidberg et al 2014), WASP-29b (Gibson et al 2013a), and HAT-P-32b (Gibson et al 2013b).…”
Section: Wavelength Dependence On the Planetary Radiussupporting
confidence: 90%
“…Also, day-side spectral features may be absent due to an isothermal pressuretemperature profile (Fortney et al 2006). These planets are consistent with other transiting exoplanet observations with flat spectra in optical wavelengths on TrES-3b , GJ 3470b (a hot Uranus; Biddle et al 2014), GJ 1214b (Bean et al 2011;Kreidberg et al 2014), WASP-29b (Gibson et al 2013a), and HAT-P-32b (Gibson et al 2013b).…”
Section: Wavelength Dependence On the Planetary Radiussupporting
confidence: 90%
“…The lack of pre-ingress baseline made our modeling of underlying systematics in the light curve (detrending) more error prone and hence increased our final error bars in the transmission spectrum. If follow-up observations confirm the flat transmission spectrum to higher significance, the spectrum of HAT-P-19b would share an important property with the spectra of other close-in gas giants of about 1000 K atmospheric temperature investigated so far (Gibson et al 2013a;Nikolov et al 2014;Line et al 2013): None of their transmission spectra can be explained by a cloud-or haze-free atmosphere model, they all show indications of an additional opacity source blocking parts of the probable atmosphere. …”
Section: Resultsmentioning
confidence: 87%
“…Both models were computed according to the system parameters of are three planets similar to HAT-P-19b in their system parameters: HAT-P-1b (Bakos et al 2007), HAT-P-12b (Hartman et al 2009), and WASP-29b (Hellier et al 2010). All these planets have roughly the mass of Saturn, roughly the size of Jupiter, and an equilibrium temperature of 1000 to 1200 K. They orbit solarlike main-sequence stars of spectral type G or K. Gibson et al (2013a) obtained an optical transmission spectrum of WASP29b around the sodium line and was able to significantly rule out a pressure-broadened absorption feature. Nikolov et al (2014) observed HAT-P-1b in the optical regime during transit and detected additional absorption at the sodium core in a 30 Å wide flux channel, but no spectral signature of the broadened line wings.…”
Section: Transmission Spectrummentioning
confidence: 99%
“…Moreover, in the last 4 years, ground-based observations have also yielded promising results (e.g. Bean et al 2010;Murgas et al 2014;Jordán et al 2013;Gibson et al 2013a). However, both space-based and groundbased data often are affected by systematic noise signals, which need to be addressed before a high quality transmission spectrum can be extracted.…”
Section: Introductionmentioning
confidence: 99%